Self-Hierarchy in Perceptual Matching: Variations in Different Processing Stages - Zheng, Yingcan; Xiao, Zilun; Liu, Yong; Zhou, Xin (Frontiers in Psychology, 2022)
People have three cognitive representations of the self, namely, the individual, relational, and collective selves, which are indispensable components of selfhood but not necessarily given equal preference. Previous studies found that people displayed varied self-hierarchy in miscellaneous tasks involving different research materials that had pre-existing learned associations established over long periods of time. Therefore, this study tries to explore a purer self-hierarchy without the influence of research materials, using perceptual matching tasks. The behavioral and event-related potentials’ (ERPs) findings showed that people recognized information association with their individual self (IS) faster compared with their relational (RS) and collective selves (CS). Smaller N2, stronger P3 and late positive complex (LPC) amplitudes were evoked during IS compared with RS and CS. However, the three selves evoked equal P2 amplitudes at the early processing stage. Moreover, CS showed a weaker advantage than RS, demonstrating a longer reaction time, lower d prime, and weaker P3 and LPC amplitudes in the parietal region. Overall, self-hierarchy during simple perceptual processing manifested as IS > RS > CS at the late processing stage but manifested as IS = RS = CS at the early processing stage. Self-hierarchy varies according to the processing stage, even without meaningful information and during the simple perception processing. This result provides direct evidence that all selves can be tagged with neutral actions, which would fit the idea of an organism attuned to self-survival at multiple processing levels.